Forecasting Analysis of Clean Water Demand at PT. Kawasan Industri Gresik Using the Time Series Method - Syakiroh, Maulidah; Jawwad, Muhammad Abdus Salam; Wijaya, Rama (Jurusan Matematika FMIPA UNM, 2024)
Fulfilling the needs and quality of clean water for each tenant in an industrial area is the responsibility of the management of the industrial area, as is the case with PT. Kawasan Industri Gresik. The monthly clean water consumption of each tenant always fluctuates, because each tenant's water needs vary according to the company's business line. Therefore, a prediction or forecasting is needed regarding clean water consumption by tenants at PT. Kawasan Industri Gresik to ensure the availability of treated water in the Water Treatment Plant (WTP) unit so that it can meet the needs of each tenant for the next 12 months. Apart from ensuring the quantity of water, the industrial area must also ensure the quality of the water to be distributed so that it remains in accordance with the required quality standards. This study regarding clean water needs is based on data on clean water consumption of tenants at PT. Kawasan Industri Gresik in 2021-2023 then forecasting is carried out using the time series method. The results of forecasting showed that the best prediction method was Double Exponential Smoothing based on the smallest Mean Absolute Percentage Error (MAPE) value is 6,66%. Comparison of forecasting results and data, the production design capacity of the Water Treatment Plant (WTP) unit is still sufficient to meet the water needs of each tenant until 2024. The quality of the water that will be distributed is in accordance with water quality standards for hygiene and sanitation purposes in accordance with Minister of Health Regulations Number 2 of 2023.